First record of weevil Romualdius scaber (Linnaeus, 1758) (Coleoptera: Curculionidae) from Novosibirskaya Oblast, Russia - Legalov, Andrei A. (Евразиатский энтомологический журнал)
The weevil Romualdius scaber (Linnaeus, 1758) of the subfamily Entiminae and the tribe Trachyphloeini, is newly recorded for Novosibirskaya Oblast, West Siberia, Russia from green plantations of two localities in the city of Novosibirsk. Photographs of this beetle’s external appearance and habitats of two localities are provided, and a distribution map of the species in West Siberia is given.